Effect of preload squatting on sprint performance in adolescent athletes - Poulos, N.; Kuitunen, S.; Buchheit, M. (New Studies in Athletics, 2010)
Training methods and warm-up practices aimed at developing high levels of muscular power have recently received significant attention from researchers and applied practitioners. One such method utilises a combination of resistance training and sports-specific movement.